Developing Canva-Assisted Problem-Based Learning Worksheets to Improve Fourth Graders’ Cognitive Skills in Science - Ade Irawan; Endang Widi Winarni; Abdul Muktadir (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
This study aims to develop a valid, practical, and effective Problem-Based Learning (PBL) worksheet assisted by the Canva application to improve fourth-grade students' cognitive learning outcomes. Using a Research and Development approach with the ADDIE model, this research was conducted involving a fourth-grade classroom teacher and students at Public Elementary School 41 Bengkulu city. Data were collected through needs analysis, observations, interviews, and cognitive tests, and subsequently analyzed using qualitative descriptive and quantitative methods. The development process resulted in a systematic worksheet design tailored to curriculum demands, emphasizing material relevance, clear instructions, and visual appeal. Expert validation indicated high feasibility, with material validity reaching 0.83, language validity at 1.00, and design validity at 1.00. Furthermore, the implementation revealed highly positive practical responses from both the teacher and students. The cognitive tests demonstrated a significant improvement, with average scores increasing from 75.50 (pretest) to 89.00 (posttest), yielding a moderate and statistically significant N-Gain score of 0.55 (p < 0.05). The findings suggest that Canva-assisted PBL digital worksheets serve as an effective, engaging instructional resource to foster active scientific inquiry and enhance cognitive outcomes in elementary education.